The Effect of GCG, Financial Performance and Firm Value on Stock Prices in the Manufacturing Sector on the IDX - Maghfirah, Nailah; Giyartiningrum, Eko (Jurnal Manajemen (Edisi Elektronik), 2024)
The capital market is a place for people who want to buy shares. Many factors can affect the rise and fall of stock prices. The purpose of this research is to identify the extent to which GCG, financial performance, and firm value affect stock prices in manufacturing companies. The sampling technique is purposive sampling based on the criteria set by the researcher and produces 82 companies, so that the sample totals 246 companies listed on the Indonesia Stock Exchange in the 2020-2022 period. GCG is proxied by institutional ownership, managerial ownership, board of directors, audit committee, and independent commissioners, while financial performance with Return on Assets (ROA) and firm value with Tobins' Q. Multiple linear regression is used as a data analysis tool. The data processing calculations in this research utilised IBM SPSS 25 software to ensure precise results. This research states that in the context of manufacturing companies on the Indonesia Stock Exchange in the 2020-2022 period, stock prices are influenced by GCG indicators proxied by the board of directors while other proxies are not. Stock prices are also influenced by financial performance. Meanwhile, firm value has no significant effect on stock prices. This research is expected to be a reference for future researchers and is expected to add variables.